Gods in the World Placemaking and Healing in the Himalayas - Jassal, Aftab S. (Religion, Culture, and Public Life, 2024)
In the north Indian state of Uttarakhand, in the Central Himalayas, Hindu deities are ever present in the lives of devotees. Through ritual practices of placemaking, spirit mediums, oracles, priests, and other specialists bring these beings into embodied form, calling on them for healing and counsel. In exchange for alleviating human suffering, deities ask that a place be made for them-in homes, villages, and temples, and in bodies, lives, and communities.Gods in the World is a richly descriptive and evocative ethnography of Hindu ritual practices that shows how deities and other supernatural agents come to matter to ordinary people. Aftab S. Jassal traces how acts of placemaking, including healing practices that repair and restore relations between people and deities, allow deities to participate and intervene in human affairs. Many of the professional healers, storytellers, musicians, spirit mediums, and lay devotees who are chronicled belong to marginalized Dalit communities. These communities are at the forefront of combined pressures of tourism, neoliberal development, and Hindutva nationalist politics and often find creative ways of responding to their changing worlds. Bringing together fresh insights on the dynamics of caste and gender with enduring questions about ritual, healing, and the nature of human-divine relations, Gods in the World offers a striking account of everyday Hinduism in a contested and rapidly changing region